PREDIKSI PERUBAHAN GARIS PANTAI AKIBAT SEDIMENTASI â EROSI DI PERAIRAN PULAU BAAI BENGKULU MENGGUNAKAN PROGRAM GENESIS - , Nina Herlina ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pulau Baai port located on the west coast of Sumatra is an alternative port, which serves as a means of sea transport and carrier strip batubara potential for domestic and export out of the cities. District wide enough and relatively safe anchorage for ships. This port shapes pool with depths towards the sea. With port shape so then ship anchored securely enough from the influence of ocean waves. Problems that often occur in this Pulau Baai port erosion and sedimentation is the availability of a fast interrupt the flow of traffic in and out of port the ship. This research is aimed to search for the shoreline change, erosionsedimentation and to find out the type of shoreâs structure as the solution. This research is done by identifying the issues, study the data and numerical model simulations using a program that generates Genesis ( generalized model for simulating shoreline change ) shoreline position and sediment transport capacity. Material used is of primary data and secondary data obtained from the relevant authorities in the form of a data bathymetry Pulau Baai port by Jakarta dishidros, wind data and wave data by meteorological and geophysics agency Pulau Baai port, and others. Based on the analysis and study, simulation program gave the result that it was the coastal area got the sedimentation which has sediments transports capacity around 1960.000 mÂ³/year. The northeast shoreline of the port would erosion about 250 meters length and was going to move the initial position of shoreline to mainland direction was about 130 meters length. In order to manage the problem, there are several alternatives used. Dredging is one of the alternatives which is quite effective and efficient because it is much easier and more economical to be implemented. Another alternative is groin building. This is the best alternative as it can reduce the sediment transports capacity around 1610.000 mÂ³/year. To protect the coastal land destruction is erosion can make the seawall building.